Review of Ratio Decidendi, the Public Prosecutor's Demands in Ultra Petita Against Criminal Law Enforcement in Indonesia - muh Nasir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Ratio Decidendi Hakim in deciding cases that are Ultra Petita in criminal law enforcement in Indonesia. Ultra Petita is a judge's decision that decides outside of the Public Prosecutor's indictment, while the background for writing this thesis is Ultra Petita's decision  which is contrary to Article 182 Paragraph (4) of the Criminal Procedure Code which states that the Judge's deliberations in his decision must be based on the indictment and everything that has been proven in the trial and in the rules of Article 183 of the Criminal Procedure Code states that the Judge in deciding the case is based on the above at least 2 (two) pieces of evidence and conviction, The problem used in this study is what  is the ratio of decidendi to the judge's ultra petita verdict  in criminal cases in Indonesia? And what are the implications of the existence of the judge's ultra petita verdict  in criminal law enforcement in Indonesia? The method used in this thesis is normative-empirical. Normative-Empirical Law Research (applied law research), which is a research that uses normative-empirical legal case studies in the form of legal behavior products, namely a combination of research on legal principles. Research on legal systematics. Research on the level of legal synchronization. Legal history research. Comparative legal research.  Meanwhile, Sociological or Empirical Law Research, which consists of: Research on legal identification. Research on legal effectiveness The results of the research The ultra petita  verdict is a decision issued by a panel of judges in a case outside the indictment of the Public Prosecutor, because it is known that the indictment was prepared incarefully so that it could not be proven in court. There are several examples of ultra petita  decisions within the framework of criminal law enforcement in Indonesia. Among them are: Decision Number: 17/Pid.Sus/TPK/2014/PN. JKT. PST related to corruption cases, Decision Number: 55/Pid.Sus/2019/Sit related to narcotics possession cases, Decision Number: 240/Pid.Sus/2021/PN. TNG related to the Narcotics case, Decision Number: 537/Pid/B/2007/PN.Jkt The team is related to the murder case, Decision Number: 314/Pid.Sus/2015/PN. Rap is related to the Narcotics case, and Decision Number: 407/Pid.Sus/2015/PN. SBY is related to a narcotics case. The six decisions are ultra petita because of the inaccuracy of the Public Prosecutor in compiling the indictment, so that in order to give a verdict to the defendant who has actually committed a criminal act, in this case the panel of judges uses other similar articles so as not to do the same. Therefore, in the perspective  of the ratio decidendi theory, judges' decisions must be able to present alternatives that can be an option in efforts to enforce justice.